CURRENCY SUBSTITUTION IN INDONESIA - Wahyu Ario Pratomo; Wiyadi Wiyadi (Benefit: Jurnal Manajemen dan Bisnis, 2009)
This article describes the phenomenon of currency exchange when there is high inflation in a countryor it’s referred to dollarization. The phenomenonof high inflation also occurred in Indonesia in recent years when the economic crisis. This article tries to examine whether there dollarization in 1997 until 2004.The results showed that there has been exchange of currency or dollarization is significant when the economic crisis and its aftermath.